TWINNING AND ITS MANAGEMENT IN MARES - SINGH, J; SINGH, R K; TANDON, S N (The Indian Journal of Animal Reproduction, 2011)
Present report records a case of twin pregnancy in mare and its successful reduction to a singleton.
Keywords: Mare; Twinning; Twin reduction